2016
DOI: 10.1128/jvi.02516-15
|View full text |Cite
|
Sign up to set email alerts
|

Specialization of Hepatitis C Virus Envelope Glycoproteins for B Lymphocytes in Chronically Infected Patients

Abstract: Hepatitis C virus (HCV) productively infects hepatocytes. Virion surface glycoproteins E1 and E2 play a major role in this restricted cell tropism by mediating virus entry into particular cell types. However, several pieces of evidence have suggested the ability of patientderived HCV particles to infect peripheral blood mononuclear cells. The viral determinants and mechanisms mediating such events remain poorly understood. Here, we aimed at isolating viral determinants of HCV entry into B lymphocytes. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In contrast, CD19 + B cells from chronic infected patients established infection in the mice whereas B cells from recently infected patients were non-infectious; highlighting a dichotomy in the infectious sources of HCV. Comparing HCV QS-diversity in the sera and B cells of these infected subjects con rmed previous reports of viral compartmentalization (nonrandom phylogenetic distribution) in B cells (48,49). The intracellular B cell compartment carried a unique population of pauci-or monoclonal viral variants that closely resembled replicating virus isolated from mice infected via B cell transfer.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, CD19 + B cells from chronic infected patients established infection in the mice whereas B cells from recently infected patients were non-infectious; highlighting a dichotomy in the infectious sources of HCV. Comparing HCV QS-diversity in the sera and B cells of these infected subjects con rmed previous reports of viral compartmentalization (nonrandom phylogenetic distribution) in B cells (48,49). The intracellular B cell compartment carried a unique population of pauci-or monoclonal viral variants that closely resembled replicating virus isolated from mice infected via B cell transfer.…”
Section: Discussionsupporting
confidence: 83%
“…To further ascertain the importance of E1-E2 proteins in the lymphotropism of SB virus, we produced HCVpp using an envelope-defective HIV-1 proviral vector495051. This HCVpp bears the E1 and E2 envelope proteins of HCV and contains a luciferase reporter gene in the lentivector.…”
Section: Resultsmentioning
confidence: 99%
“…lymphotropism was recently provided which showed that a distinct virus subpopulation capable of encoding particular E1E2 (envelope) epitopes might be responsible for the infection of B lymphocytes [86]. Isolated HCV E1E2 glycoproteins from patient B cells were able to confer the ability to enter and replicate in B cells to a non-lymphotropic HCV JFH-1 strain, as demonstrated by the detection of viral RNA and proteins within those cells.…”
Section: An Important Finding Toward the Recognition Of Virological Dmentioning
confidence: 99%